Analysis and characterization of microstructural evolutions, mechanical response and fracture mechanism of laser welded Fe–Co–V ultra-thin foils. (May 2015) - Mostaan, H.; Shamanian, M.; Monirvaghefi, S.M.; Behjati, P.; Hasani, S.; Fathi Moghaddam, M.; Amiri, M.; Szpunar, J.A.
Abstract: The welding behavior of the Fe–Co–7 wt% V ultra-thin foils was examined using the Nd:YAG laser welding method. Scanning electron microscopy and electron backscattered diffraction were used to investigate microstructural changes and fracture mechanism of the weld joints. Tensile test and microhardness measurement were employed in order to study the mechanical behaviors of the welds. Microstructural observations indicated that a bimodal grain size distribution is seen in the fusion zone. It was found that the fracture surfaces of the welds consist of both cleavage sites and dimples. It was also revealed that the cleavage sites are mainly located in the coarse grain zone while numerous dimples are located in the fine grain zone. Considering the phase transformations which occur in the base metal, variation of the microhardness in different regions of the welds was discussed. The results demonstrated that the fusion zone and heat affected zone of welded samples experience a significant decrease in their hardness. Highlights: Due to the formation disordered structure, hardness of HAZ and FZ was lower than BM. All of the welded specimens fractured in the FZ. Sample with higher EPPD had higher UTS owing the formation of smoother weld bead.